MENYEGEL ‘RUMAH TUHAN’: Menakar Kadar Kemaslahatan Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri No. 9/ 2006 dan No. 8/2006 dalam Mereduksi Konflik Pendirian Rumah Ibadah di Indonesia - Asroni, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2012)
The Indonesian government officially issued joint decrees of the Min- ister of Religious Affairs No. 9/2006 and of the Minister of Home Affairs No. 8/2006 which regulate procedures and requirements for building house of worship. However, this regulation is deemed as the state inter vention and discrimination towards certain religious mi- nority groups. In many places, this regulation generates conflict among belivers. This regulation is often used by religious radical groups to eliminate the right of building house of worship.This paper discusses the background of the issuance of the regula- tion and analyzes it critically. In addition, this paper proposes conflict resolution of house of worship in Indonesia.